2014
DOI: 10.1002/cbic.201402420
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Amyloid Fiber Formation in the N Terminus of Androgen Receptor

Abstract: Most of the biological effects of androgen hormones are mediated through an intracellular transcription factor, the androgen receptor (AR). This protein presents a long disordered N-terminal domain (NTD), known to aggregates into amyloid fibers.1 This aggregation property is usually associated with the presence of a poly-glutamine tract (polyQ), known to be involved in several pathologies.2 The NTD has gain interest recently because potential anti-prostate-cancer molecules could target this domain.3 Here, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…This was confirmed by transmission electron microscopy (TEM) analysis of the pelleted material in the NMR tube after the 24 h incubation. The resulting images displayed numerous fibrils with a large distribution of lengths but similar widths in agreement with our previous report [14]. …”
Section: Amyloidogenic Properties Of Kelckavsvsm Peptides Expressed Asupporting
confidence: 91%
See 3 more Smart Citations
“…This was confirmed by transmission electron microscopy (TEM) analysis of the pelleted material in the NMR tube after the 24 h incubation. The resulting images displayed numerous fibrils with a large distribution of lengths but similar widths in agreement with our previous report [14]. …”
Section: Amyloidogenic Properties Of Kelckavsvsm Peptides Expressed Asupporting
confidence: 91%
“…We have previously shown that the KELCKAVSVSM forms fibrils under mild oxidation conditions [14]. We therefore determined whether the SUMO-KELCKAVSVSM fusion proteins (either in the monomer or dimer form) would form amyloid fibers but this failed after repeated attempts.…”
Section: Amyloidogenic Properties Of Kelckavsvsm Peptides Expressed Amentioning
confidence: 97%
See 2 more Smart Citations
“…Hereafter, we refer to this 11 residue sequence as P11 . We have recently shown that the oxidation of Cys240 promoted the formation of peptide amyloid fibers, a process that can be reversed by the addition of a reducing agent such as tris(2-carboxyethyl)phosphine (TCEP) [13]. …”
Section: Introductionmentioning
confidence: 99%